Membangun Pribadi Yang Bersih dan Jujur - Zumrotil Auliya; Indah Dewi Permata Sari; Ilham Hudi; Rini Febrianti; Alya Aqilla; Lily Ervina Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to identify factors that influence the formation of a clean and honest personality and to instill these values from an early age to form a positive character. The method used is a Systematic Literature Review (SLR), by investigating 30 journal articles published from 2020 - 2024. This research shows that strengthening the value of honesty must start from an early age through character education in families and schools, and is supported by government policies that are firmly against corrupt practices. The results of this research can be a basis for further research in this field and can help develop an understanding of the complexity of anti-corruption issues in Indonesia. Future research could focus on developing anti-corruption education strategies from an early age and evaluating the effectiveness of existing policies